Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12866-020-01941-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial pattern of endophytic fungi diversity of Camellia sinensis (cv. Shu Cha Zao)

Abstract: Background: The experimental materials were a 60-year-old tea tree (Camellia sinensis cv. Shu Cha Zao; SCZ) (the mother plant) and 1-year-old and 20-year-old plants of SCZ that originated as mother plant cuttings. The aim of this study was to use high-throughput sequencing to study the spatial and dynamic distribution of endophytic fungi in different leaf niches (upper leaves, middle leaves, lower leaves) and rhizosphere soil on tea plants of different ages in the same garden. Results: Ascomycota (83.77%), Bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
(42 reference statements)
6
21
0
Order By: Relevance
“…However, despite the long-term plantation over 100 years, the bacterial community abundance and diversity kept stable in ancient tea plantations because of the natural cultivation way that maintained relatively higher soil fertility. The significantly ( P < 0.05) higher fungal abundance and diversity in ancient tea plantations was consistent with the report by Wu et al (2020) [ 38 ], which confirmed that the long-term plantation might improve the fungal community in rhizosphere soil.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, despite the long-term plantation over 100 years, the bacterial community abundance and diversity kept stable in ancient tea plantations because of the natural cultivation way that maintained relatively higher soil fertility. The significantly ( P < 0.05) higher fungal abundance and diversity in ancient tea plantations was consistent with the report by Wu et al (2020) [ 38 ], which confirmed that the long-term plantation might improve the fungal community in rhizosphere soil.…”
Section: Resultssupporting
confidence: 91%
“…The dominant phyla in fungal community composition were consistent with the report by Wu et al (2020) [ 38 ]. The abundances of Ascomycota and Mortierellomycota phyla, as well as 9 genera (i.e.…”
Section: Resultssupporting
confidence: 91%
“…However, despite the long-term plantation over 100 years, the bacterial community abundance and diversity kept stable in ancient tea plantations because of the natural cultivation way that maintained relatively higher soil fertility. The signi cantly (P<0.05) higher fungal abundance and diversity in ancient tea plantations was consistent with the report by Wu et al (2020) [38], which con rmed that the long-term plantation improve the fungal community in rhizosphere soil.…”
Section: Soil Microbial Community Abundance Diversity In Various Teasupporting
confidence: 90%
“…The dominant phyla in fungal community composition were consistent with the report by Wu et al (2020) [38]. The abundances of Ascomycota and Mortierellomycota phyla, as well as 9 genera (i.e.…”
Section: Fungal Community Composition In Modern and Ancient Tea Plantationssupporting
confidence: 89%